COVID-19, lockdown and (disability) sport. Issue 1 (4th March 2022) - Fitzgerald, Hayley; Stride, Annette; Drury, Scarlett
ABSTRACT : A number of recent Managing Sport and Leisure commentaries have explored how COVID-19 is touching sport. Our commentary adds to these discussions by considering COVID-19, lockdown and (disability) sport. This is especially pertinent given the positioning of disabled people as particularly "vulnerable" in relation to current political discourse. Four key points of discussion are focused upon. First, we explore how the media has attended to issues concerning (disability) sport during lockdown. Second, consideration is given to how sporting and physical activity opportunities have been promoted during lockdown. Third, we focus on the notion of inclusion and explore the ways in which this has thrived during lockdown. Fourth, attention is given to community (disability) sport post-lockdown and what this may mean for disability sport. We conclude by arguing that the future legacy of lockdown and COVID-19 will tell us much about how disabled people have really been embraced within sport.